2015
DOI: 10.1021/acs.jpcc.5b04658
|View full text |Cite
|
Sign up to set email alerts
|

Charge Mediated Semiconducting-to-Metallic Phase Transition in Molybdenum Disulfide Monolayer and Hydrogen Evolution Reaction in New 1T′ Phase

Abstract: The phase transition of single layer molybdenum disulphide (MoS 2 ) from semi-conducting 2H to metallic 1T and then to 1T' phases, and the effect of the phase transition on hydrogen evolution reaction (HER) are investigated within this work by density functional theory. Experimentally, 2H-MoS 2 has been widely used as an excellent electrode for HER and can get charged easily. Here we find that the negative charge has a significant impact on the structural phase transition in a MoS 2 monolayer. The thermodynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
328
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 324 publications
(347 citation statements)
references
References 71 publications
13
328
0
6
Order By: Relevance
“…It is notable that the total energy of 1T-MoS 2 is much higher than that of 1H-MoS 2 by 0.8 eV41. However, the 1 H to 1 T phase transition can be driven by lowering the energy barrier via the charge injection of electron irradiation42.…”
Section: Resultsmentioning
confidence: 99%
“…It is notable that the total energy of 1T-MoS 2 is much higher than that of 1H-MoS 2 by 0.8 eV41. However, the 1 H to 1 T phase transition can be driven by lowering the energy barrier via the charge injection of electron irradiation42.…”
Section: Resultsmentioning
confidence: 99%
“…In 2H MoS 2 (semiconducting phase), the Mo atom layer in hexagonal MoS 2 is sandwiched between S layers with a trigonal prismatic coordination of Mo atom . By contrast, the tetragonal MoS 2 , marked as ordered 1T MoS 2 or distorted 1T′ MoS 2 (metallic phase), has an octahedral coordination of Mo atoms . Based on this structural difference, the semiconducting and metallic MoS 2 exhibit different properties, which has been discussed elaborately in the following paragraphs.…”
Section: Atomic Structure and Bandgapmentioning
confidence: 99%
“…However, it should be noted that the perfect 1T phase is metastable and sometimes such a structure is dynamically unstable 97 . Recently, Du et al 99 reported a phase transition method, in which through a negative charge injection method, semiconducting 2H-MoS2 was transformed to metallic 1T MoS2 and further distorted into the 1T′-MoS2 phase. Revealed by the work of Kuo et al 98 , the basal plane of 1T′-MX2 (M = Mo, W; X = S, Se, Te) 2D materials had lower energy and were more stable than the corresponding 1T counterparts.…”
Section: Metal Sulfide and Selenidesmentioning
confidence: 99%